A Systems-Based Practice Curriculum in Orthopaedics: Successes and Challenges Moving Forward. (2nd January 2019) - Hacken, Brittney; Jarvis-Selinger, Sandra S.; Armstrong, April D.; Black, Sarah; Pratt, Daniel; Black, Kevin P.
Abstract : Background: Teaching and assessment of the systems-based practice competency have been a challenge for many educators in graduate medical education. Previous research done at our institution demonstrated a marked inconsistency across institutions in educational content, methods of delivery, and performance assessment. As a result, we developed a 2-week health systems curriculum for orthopaedic surgery residents. Methods: A 2-week health systems rotation was developed during which postgraduate year (PGY)-1 residents were excused from their normal clinical duties. Residents followed patients as observers of the health-care system, challenged to view health care through the eyes of the patient and to identify what could be done individually and collectively to provide a better and safer experience. Additional learning experiences were designed on the basis of our literature review. At the end of the rotation, residents discussed and provided a written summary of their experiences and completed an anonymous evaluation. Using a Likert scale (1 to 10), residents were asked if the experience was educational and whether it was it additive to their undergraduate medical education for each of the 9 educational areas. Results: The mean responses for all 9 educational areas were 8.2 for whether the experience was educational and 8.3 for whether it was it additive to participants' undergraduate medical education. Feedback from residents indicated that they found the course very helpful and that it inspired them to consider how they could "create overdue and necessary changes in our health-care system." Conclusions: Our health systems rotation in PGY-1 has been a valuable learning experience for the residents and has created a foundation on which to build in subsequent years of residency.